KEARIFAN LOKAL MEMPERTAHANKAN “MAHAVANA” DALAM MENUNJANG PENGEMBANGAN AGROWISATA DI DESA JATILUWIH KECAMATAN PENEBEL KABUPATEN TABANAN - Sarjana, I Made (Bumi Lestari, 2012)
It is a fact that the people in Jatiluwih together with local government of Tabanan Regency have been conserving 1.299,687 hectars of their forest. It was motivated since the forest has a vital role on producing fresh air and water for local people. Data was collected through e.g. indepth interview, observation and literature study. This article described the lesson learned from community of Jatiluwih on concerving their forest based on local genious. Result of the research showed that Jatiluwih Community implemented three methods on preserving their forest. They are called wanasri such as: (1) mahavana, very restricted area, people are forbidden to cut down any tree, (2) tapawana, people allowed to change function to this area just for building tample, (3) srivana, allowed for changing of land usage, such as for farming activity, or building (house, school, poultry etc). Beside ecological role, the forest in Jatiluwih also has economic impact on increasing their quality of life. It has also been becoming one of the tourist attraction or agrotourism object
Keywords: local genious, mahavana, agrotourism